Pengembangan Sistem Kunci dan Bell Pintu Berbasis WiFi Menggunakan ESP32-CAM Terintegrasi Telegram - Merilsafani; Wahda Tulummah; Elin (Journal Electric Field, 2024)
Home security is a major concern in the era of modern technology. This study aims to develop a WiFi-based door lock and doorbell system using ESP32-CAM integrated with Telegram. This system is designed to provide an efficient security solution, allowing users to receive real-time notifications and control door access remotely through the Telegram application. The research methods are hardware design, software development, and integration of the IoT module with Telegram. The test results show that the system operates effectively in sending images in tests I-III obtained 5-7 seconds, sending notifications when the doorbell button is pressed with a time of 4-6 seconds, testing distances of 10 cm, 13 cm, and 15 cm, and an error value of 0.1-0.3%. This implementation is expected to improve home security with an easily accessible and reliable technological approach.